Analisis Minimnya Partisipasi Politik Perempuan Bali pada Kursi Dewan dari Perspektif Hubungan Sosial Masyarakat Adat Bali (Studi Kasus: DPRD Provinsi Bali) - Putu Villian Pramesti Swara (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2023)
This research is entitled "Analysis of the Lack of Political Participation of Balinese Women in Board Chairs from the Perspective of Social Relations of the Balinese Indigenous People (Case Study: DPRD Bali Province)". Patriarchal culture is often an obstacle for women in their activities, especially in the political field. As we know, women's participation in politics is arguably still minimal, and sometimes it can't meet the quota of women themselves. The limitations of women's participation can be seen in the social lives of people who are still infested by a patriarchal culture. From a socialist feminism standpoint, this paper aims to explore the underrepresentation of women in elected positions in the Bali Provincial DPRD. With the help of key informants and literature reviews, this study employs a type of qualitative descriptive research. By contrasting the data acquired from several different documents, the data triangulation procedure was carried out.